Nasal Reconstruction: Defects that Cross Anatomical Subunits - Iorio, Caitlin Boling; Christophel, J. Jared; Park, Stephen S. (Facial Plastic Surgery, 2020)
The nose plays a crucial role in the human experience, both aesthetically and functionally. The biomechanics of covering flaps, the importance of a firm framework, and the anatomical basis for aesthetic subunits are imperative concepts as one proceeds through the algorithm of reparative options. The subunits consist of three paired units—the ala, soft tissue facets (also known as soft tissue triangles), and sidewall, as well as three unpaired units—the dorsum, tip, and columella. Because many defects cross aesthetic subunits, it is critical to understand when to adapt the subunit principle and how or when to use a combination of techniques. It can be more challenging to apply the subunit principle to small grafts and local flaps of the nose. Convex subunits, such as the nasal tip and alar lobule, more frequently follow the subunit principle. In our practice, we adhere to a teaching of producing “straight lines and sharp corners.” This applies to local flaps and grafts and focuses on keeping scar lines inconspicuous. In this article, we discuss approaches we follow for various defects along with technical pearls for performing these reconstructions. The subunit principle is more of a practice of thinking of resultant scars within a background of existing lines, reflections, and contour inflections.
Keywords: subunits; nasal reconstruction; aesthetic subunits